(untitled) (Reflection and Critique Law Magazine, 2020)
Against the technological innovations and the consequent ease of news sharing, whether by the press or by ordinary people, who everyday more have the most modern media at their fingertips, the right to be forgotten returns to the center of debate. Then comes up an obstacle, on the one hand the freedom of expression, information and press, fundamental rights consecrated by the Democratic State of Law and indispensable for a democratic society, which cannot go under any kind of censorship, and on the other hand, the rights of the personality, constitutionally assured and inherent to the men lives dignity, with emphasis on the right to be forgotten that protects the private life of the individuals. The right to be forgotten, for those who admit the existence of this right of personality, would not be able to erase facts or rewrite stories, but rather to ensure that news that has already been widely disseminated is not transmitted again tirelessly in time because society by itself has already tried to forget and lost interest in the fact. In this present study a critical analysis will be done about this institute that shows itself quite relevant nowadays, culminating in a recent decision of the Federal Supreme Court though.